Systematic review of shift work and nurses' health. (27th May 2019) - Rosa, D; Terzoni, S; Dellafiore, F; Destrebecq, A
Abstract: Background: Nursing is characterized by a working articulation in shifts to ensure continuity of care throughout the 24 h. However, shift work and the resulting desynchronization of circadian rhythms may have adverse effects on nurses' health. Aims: To describe the effects of shift work and desynchronization of circadian rhythms on nurse's health. Methods: Databases : PubMed, Cinahl, Scopus, Embase and Ilisi. Search terms (free terms, MeSH): 'nurses', 'shiftwork', 'nightwork', 'sleep disorder, circadian rhythm', 'work schedule tolerance', 'breast neoplasm', 'metabolic syndrome X', 'metabolic cardiovascular syndrome', 'Cardiovascular disease', 'stress', 'diabetes'. We included all randomized controlled trials, observational studies, reviews and papers studying nurses' shift work. Quality assessment of the retrieved papers was verified according to Dixon-Woods checklist. Results: Twenty-four articles were analyzed. Literature review has shown that shift work involves an alteration in psychophysical homeostasis, with a decrease in performance. It is an obstacle for social and family relationships, as well as a risk factor for stress, sleep disorders, metabolic disorders, diabetes, cardiovascular disorders and breast cancer. Conclusions: An organized ergonomic turnaround can be less detrimental to the health of nurses and more beneficial for the healthcare providers. Therefore, we suggest organizing studies to assess whether improving nurses' health would lead to a reduction in miscarriages, absenteeism and work-related stress.